Research Of Market Maturity Phases Of Energy Technologies - Rafailovich Sadriev, Azat (2019)
The article discusses the patterns in the market positioning of various energy technologies and identifies technological developments that are residing in the early stages of the market maturity cycle. The study is based on the use of the Hype Cycle conceptual platform and methods of cluster and classification analysis, the functionality of which is implemented using the Mclust software package from the realm of the programming language R. The information on patent and publication activity presented in global search engines Google Patents and Google Scholar has served as the informational basis for the analytical procedures conducted. The main provisions of the study were tested on the example of transformers for a voltage of 220 kV. For this technological development, its critical structural elements are identified, including heat exchangers with forced circulation of oil (air), oil-air coolers, on-load tap-changers, bushings with the main insulation of the porcelain tire, and bushings with gas insulation, each of which is analyzed from the point of view of existing patterns of its positioning on the Hype Cycle. It has been established that most of these structural elements are within the framework of the “slope of enlightenment” and “plateau of productivity” phases, which characterizes the energy technology under study as already established one, which, in combination of its characteristics, goes beyond the developments of an innovative profile.